Fat intake and risk of ulcerative colitis: Systematic review and dose–response meta‐analysis of epidemiological studies. Issue 1 (January 2017) - Wang, Fan; Lin, Xue; Zhao, Qiu; Li, Jin
Abstract: Background and Aim: Fat intake is generally thought as a risk factor for onset of ulcerative colitis (UC), while epidemiological data had been controversial. This study aimed to evaluate the role of fat intake in the development of UC. Methods: Comprehensive search in PubMed and Embase was conducted to identify all relevant studies, and the role of fat intake in the development of UC was quantitatively assessed by dose–response meta‐analysis. Results: Nine studies (four case–control and five prospective cohort) were indentified with a total of 966 UC cases and 171 589 controls. No evidence of a nonlinear dose–response association was found between fat intake and UC risk. Overall, the summary relative risks (RR) for per 30 g increment/day were 1.023 (95%confidence interval [CI]: 0.963–1.087; I 2 = 24%; n = 6) for total fat intake, 1.063 (95%CI: 0.845–1.337; I 2 = 44.5%; n = 4) for saturated fat intake, 1.214 (95%CI: 0.911–1.618; I 2 = 63.1%; n = 4) for monounsaturated fat (MUFA) intake, and 1.247 (95%CI: 0.948–1.640; I 2 = 25.4%; n = 4) for polyunsaturated fat (PUFA) intake, respectively. Subgroup and sensitivity analyses showed inconsistent results on PUFA intake, which was significantly related with UC risk after adjusting for smoking (RR: 1.617, 95%CI: 1.045–2.502; I 2 = 0%; n = 3). For PUFA and MUFA subtypes, no subtypes were significantly associated with UC risk ( P > 0.05), and only docosahexaenoic acid showed a potential protective effect in the development of UC (RR for the highest versus lowest intake level: 0.642, 95%CI: 0.403–1.024; I 2 = 34.4%; n = 3) Conclusions: This meta‐analysis suggested a lack of association between fat intake and UC risk, and large‐scale prospective designed studies are warranted to confirm our findings.